2014
DOI: 10.7150/jca.9388
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis on Small Cell Carcinoma of the Prostate in Chinese Patients

Abstract: Objective: To explore the clinical and pathological characteristics of small-cell carcinoma (SmCC) of the prostate and applicable treatment methods. Methods: We reported three cases of SmCC of the prostate diagnosed from 1999 to 2011 at the Chinese PLA General Hospital. We also reviewed clinical and pathological data of 26 cases in China reported over the same period. Results: Serum prostate-specific antigen (PSA) levels were normal in 20 cases (76.9%) and elevated in six (23.1%). There was local invasion in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 10 publications
(13 reference statements)
1
19
1
Order By: Relevance
“…In this study, we stratified the treatments based on summary stage and found that chemotherapy improved the survival of patients with distant/regional metastasis but not patients with localized tumor. These results agreed with the findings of other studies, in which they demonstrated chemotherapy is beneficial to patients with prostate SCC …”
Section: Discussionsupporting
confidence: 93%
“…In this study, we stratified the treatments based on summary stage and found that chemotherapy improved the survival of patients with distant/regional metastasis but not patients with localized tumor. These results agreed with the findings of other studies, in which they demonstrated chemotherapy is beneficial to patients with prostate SCC …”
Section: Discussionsupporting
confidence: 93%
“…3,6 Additional randomized trials have explored the addition of other systemic agents with limited to no benefit. 2,10 A research report that explored the clinical and pathological characteristics of SCC of the prostate found statistical evidence that survival time was closely related to chemotherapy administration. The one-year survival rate for patients treated with chemotherapy was 50% while those who did not receive treatment was 9%.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, including age, were not statistically significant when correlated with survival time. 2,6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations